Risk of intracerebral haemorrhage from hypertension is greatest at an early age. (March 2021) - Stanton, Robert; Demel, Stacie L; Flaherty, Matthew L; Antzoulatos, Eleni; Gilkerson, Lee A; Osborne, Jennifer; Behymer, Tyler P; Moomaw, Charles J; Sekar, Padmini; Langefeld, Carl; Woo, Daniel
Introduction: The risk of intracerebral haemorrhage (ICH) associated with hypertension (HTN) is well documented. While the prevalence of HTN increases with age, the greatest odds ratio (OR) for HTN as a risk for ischemic stroke is at an early age. We sought to evaluate if the risk for ICH from HTN was higher in the youngest patients of each race. Patients and methods: The Ethnic/Racial Variations of ICH (ERICH) study is a prospective multicenter case-control study of ICH among whites, blacks, and Hispanics. Participants were divided into age groups based on race-specific quartiles. Cases in each race/age group were compared to controls using logistic regression (i.e., cases and controls unmatched). The probability of ICH among cases and controls for each race were compared against independent variables of HTN, quartile of age and interaction of quartile and age also using logistic regression. Results: Overall, 2033 non-lobar ICH cases and 2060 controls, and 913 lobar ICH cases with 927 controls were included. ORs were highest in the youngest age quartile for non-lobar haemorrhage for blacks and Hispanics and highest in the youngest quartile for lobar haemorrhage for all races. The formal test of interaction between age and HTN was significant in all races for all locations with the exception of lobar ICH in whites (p = 0.2935). Discussion: Hypertension is a strong independent risk factor for ICH irrespective of location among persons of younger age, consistent with the hypothesis that first exposure to HTN is a particularly sensitive time for all locations of ICH.